Carbon ion beam is more effective to induce cell death in sphere-type A172 human glioblastoma cells compared with X-rays. (December 2014) - Takahashi, Momoko; Hirakawa, Hirokazu; Yajima, Hirohiko; Izumi-Nakajima, Nakako; Okayasu, Ryuichi; Fujimori, Akira
Abstract: Purpose : To obtain human glioblastoma cells A172 expressing stem cell-related protein and comparison of radiosensitivity in these cells with X-rays and carbon beam. Methods : Human monolayer-type A172 glioblastoma cells were maintained in normal medium with 10% bovine serum. In order to obtain sphere-type A172 cells the medium was replaced with serum-free medium supplemented with growth factors. Both types of A172 cells were irradiated with either X-rays or carbon ion beams and their radiosensitivity was evaluated. Results : Serum-free medium induced expression of stem cell-related proteins in A172 cells along with the neurosphere-like appearance. These sphere-type cells were found resistant to both X-rays and carbon ion beams. Phosphorylation of histone H2A family member X persisted for a longer period in the cells exposed to carbon ion beams than in those exposed to X-rays and it disappeared quicker in the sphere type than in the monolayer type. Relative radioresistance of the sphere type cells was smaller for carbon ion beams than for X-rays. Conclusions : We demonstrated that glioblastoma A172 cells with induced stem cell-related proteins turned resistant to irradiation. Accelerated heavy ion particles may have advantage over X-rays in overcoming the tumor resistance due to cell stemness.